Spiritual Well-being, Diabetes Burden, Self-management, and Glycemic Control Among Patients with Type 2 Diabetes in Turkey: A Descriptive and Correlational Study - ÇELİK, MELİKE (My University, 2023)
Spiritual well-being is considered a significant factor in helping to manage chronic diseases and cope with the disease process. This descriptive-correlational study aimed to investigate the relationship between spiritual well-being, diabetes burden, self-management, and among 300 outpatients with type 2 diabetes in Turkey. A significant relationship was found between the diabetes burden and self-management levels and the spiritual well-being of patients with diabetes (p < 0.005). Multiple linear regression analyses found that a high diabetes burden (ß = −0.106) decreased well-being, and high self-management increased well-being (ß = 0.415). Additionally, the results revealed that marital status, household members, performing daily life activities alone, hospitalization due to complications, diabetes burden, self-management, glycemic control, and blood lipid parameters explained 29% of the total variance in the spiritual well-being level. Accordingly, the present study recommended that health professionals should consider spiritual well-being to support disease management with a holistic approach to diabetes patients.
Keywords: Tıp; Hemşirelik; Sosyal ve Beşeri Bilimler; İlahiyat; Sağlık Bilimleri; Medicine; Nursing; Social Sciences and Humanities; Theology; Health Sciences; Klinik Tıp (MED); Sanat ve Beşeri Bilimler (AHCI); Klinik Tıp; Sanat ve Beşeri Bilimler; HEMŞİRELİK; DİN; Clinical Medicine (MED); Arts & Humanities (AHCI); CLINICAL MEDICINE; ARTS & HUMANITIES; NURSING; RELIGION; Genel Hemşirelik; Dini çalışmalar; Sosyal Bilimler ve Beşeri Bilimler; General Nursing; Religious Studies; Social Sciences & Humanities; Diabetes burden; Glycemic control; Self-management; Spiritual well-being; Type 2 diabetes